Does Islamic Work Ethics Matter in The Influence of Green Entrepreneurial Orientation and Digital Orientation on Green Performance? - Arumsari, Anita Yefti; Santosa, Mulato (Innovation, Technology, and Entrepreneurship Journal, 2026)
This research aims to test and analyze the influence of green entrepreneurial orientation and digital orientation on green performance, with Islamic work ethics as a moderating variable. The population of this study consists of MSME actors residing in or operating their businesses in the city of Magelang. The sampling technique used is Purposive Sampling, with a sample of 108 respondents. The analytical tool used is data analysis through the Excel computer program for tabulation, assisted by the WarpPLS 7.0 software. The results of this study show that green entrepreneurial orientation has a positive and significant effect on green performance. Digital orientation also has a positive and significant effect on green performance. Additionally, Islamic work ethics does not moderate the relationship between green entrepreneurial orientation and digital orientation on green performance.